Anti-BCMA and GPRC5D bispecific antibodies in relapsed/refractory primary plasma cell leukemia: a case report - Bernardi, Chiara; Beauverd, Yan; Tran, Thien An; Maulini, Marie; Mappoura, Maria; Morin, Sarah; Simonetta, Federico; Cairoli, Anne; Auner, Holger W.; Samii, Kaveh; Chalandon, Yves; de Ramon Ortiz, Carmen (Frontiers in Immunology, 2024)
Plasma cell leukemia (PCL) is an aggressive and high-risk variant of multiple myeloma (MM) with a very poor prognosis. Given its rarity and aggressiveness, there is a lack of clinical trials testing the efficacity of novel therapies in these patients. New immune approaches such as B-cell maturation antigen (BCMA) and G protein-coupled receptor, family C, group 5, member D (GPRC5D) -targeting agents, including chimeric antigen receptor (CAR) T-cells and bispecific antibodies could play a role in PCL treatment. However, PCL patients were excluded from recent pivotal clinical trials testing those agents and only some case reports have been published. We present here the clinical course of a patient with relapsed/refractory (R/R) primary (p) PCL who was treated with anti-BCMA and anti-GPRC5D bispecific antibodies at our center.